Cytotoxic lymphocytes and atherosclerosis: significance, mechanisms and therapeutic challenges - Kyaw, Tin (Br J Pharmacol, 2017)
Cytotoxic lymphocytes encompass natural killer lymphocytes (cells) and cytotoxic T cells that include CD8+ T cells, natural killer (NK) T cells, γ, δ (γδ)‐T cells and human CD4 + CD28− T cells. These cells play critical roles in inflammatory diseases and in controlling cancers and infections. Cytotoxic lymphocytes can be activated via a number of mechanisms that may involve dendritic cells, macrophages, cytokines or surface proteins on stressed cells. Upon activation, they secrete pro‐inflammatory cytokines as well as anti‐inflammatory cytokines, chemokines and cytotoxins to promote inflammation and the development of atherosclerotic lesions including vulnerable lesions, which are strongly implicated in myocardial infarctions and strokes. Here, we review the mechanisms that activate and regulate cytotoxic lymphocyte activity, including activating and inhibitory receptors, cytokines, chemokine receptors‐chemokine systems utilized to home to inflamed lesions and cytotoxins and cytokines through which they affect other cells within lesions. We also examine their roles in human and mouse models of atherosclerosis and the mechanisms by which they exert their pathogenic effects. Finally, we discuss strategies for therapeutically targeting these cells to prevent the development of atherosclerotic lesions and vulnerable plaques and the challenge of developing highly targeted therapies that only minimally affect the body's immune system, avoiding the complications, such as increased susceptibility to infections, which are currently associated with many immunotherapies for autoimmune diseases. LINKED ARTICLES: This article is part of a themed section on Targeting Inflammation to Reduce Cardiovascular Disease Risk. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.22/issuetoc and http://onlinelibrary.wiley.com/doi/10.1111/bcp.v82.4/issuetoc